Optical Characterization of Different Thin Film Module Technologies. (8th June 2015) - Ebner, R.; Kubicek, B.; Újvári, G.; Novalin, S.; Rennhofer, M.; Halwachs, M.
Abstract : For a complete quality control of different thin film module technologies (a-Si, CdTe, and CIS) a combination of fast and nondestructive methods was investigated. Camera-based measurements, such as electroluminescence (EL), photoluminescence (PL), and infrared (IR) technologies, offer excellent possibilities for determining production failures or defects in solar modules which cannot be detected by means of standard power measurements. These types of optical measurement provide high resolution images with a two-dimensional distribution of the characteristic features of PV modules. This paper focuses on quality control and characterization using EL, PL, and IR imaging with conventional cameras and an alternative excitation source for the PL-setup.